CIPP Evaluation of Differentiated Learning in Elementary School: Evaluasi Pembelajaran Berdiferensiasi Berbasis CIPP di Sekolah Dasar - Anna Roosyanti; Diyas Age Larasati (Pedagogia : Jurnal Pendidikan, 2026)
General Background: Differentiated learning supports inclusive practices within the Merdeka Curriculum in elementary education. Specific Background: SDN Babatan IV 459 Surabaya has implemented differentiated learning without prior systematic evaluation. Knowledge Gap: Limited studies apply the CIPP (Context, Input, Process, Product) model to evaluate differentiated learning in inclusive elementary settings. Aims: This study evaluates the implementation of differentiated learning using the CIPP framework. Results: Through qualitative methods involving observation, interviews, and document analysis, findings indicate adaptive curriculum design, diverse learning resources, responsive strategies, and active teacher–student interaction aligned with varied learning profiles, including students with intellectual disabilities. Improvements were identified in conceptual understanding, critical thinking skills, learning motivation, and reduction of learning gaps in heterogeneous classrooms. Novelty: The study applies a structured CIPP evaluation to differentiated learning in an inclusive elementary school context. Implications: Systematic evaluation through CIPP supports sustainable inclusive pedagogy and adaptive curriculum implementation. Highlights:• Comprehensive CIPP analysis demonstrates adaptive and inclusive classroom practices across context, input, process, and product components.• Flexible curriculum design and varied instructional resources accommodate diverse learning profiles, including students with intellectual disabilities.• Observable gains in conceptual mastery, higher-order reasoning, and classroom participation were identified. Keywords: Differentiated Learning; CIPP Evaluation Model; Inclusive Education; Elementary School; Merdeka Curriculum